Trials of Apollo: Hidden Oracle - Riordan, Rick (London Penguin Random House UK, 2016)
The latest series from international bestselling author, Rick Riordan. He was once an immortal God. Now, he's a teenage boy called Lester. Apollo has angered his father Zeus for the last time. So, how do you punish an immortal. By making him human. Obviously. Cast down from Olympus, he's weak, disorientated and stuck in New York City as a teenage boy.
Keywords: English Fiction; Novel- English